(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the effects of chicken slaughter methods with electronarcosis and without stunning (according to the Halal method) and unilateral and bilateral cuts on exsanguination efficiency. A total of 100 female fowls were slaughtered under the Federal Inspection Service and divided into two treatments: with and without stunning, subjected to two different handling protocols: unilateral and bilateral cuts of the carotid arteries and veins in a completely randomized design. Exsanguination efficiency was assessed by means of the percentage of blood drained by body weight of the chickens expelled through unilateral and bilateral cuts of blood vessels. Greater blood loss was observed in slaughtered animals stunned by electronarcosis, and there was no statistical difference between unilateral and bilateral cuts. In conclusion, from the point of view of exsanguination efficiency, the slaughter method with electronarcosis does not impair blood flow, in compliance with the Halal slaughter precepts.